Childhood sexual abuse : the Red Cross War Memorial Children's Hospital experience, 1986-1988 - McKerrow, Neil Hugh (Department of Paediatrics and Child Health, 2018)
This retrospective descriptive study reviews sexually abused children who presented to the Child Abuse Team at the Red Cross War Memorial Children's Hospital (RCWMCH) between 1 January 1986 and 31 June 1988. During this period 365 children were referred to the Child Abuse Team, of whom 357 were entered into this study. 297 of these were cases of confirmed sexual abuse. There were 48 male children and 123 children under 6 years of age. Most children were victims of a single episode of sexual abuse with only 13, 7% presenting following repeated abuse. More serious forms of sexual abuse, rape or sodomy, were common, accounting for 60% of the cases. Over 70% of the children had physical signs to substantiate their claims of having been sexually abused. Sexually transmitted disease was a common finding, being present in 15,6 % at presentation. All children were accompanied to hospital by an adult, usually a parent. 60% of the children presented directly to RCWMCH. A delay between abuse and presentation was common, only 42% of the children presenting within 48 hours of having been abused. Physical problems frequently required management. Very few children received more than crisis intervention for their emotional state and only 20% needed any form of intervention to ensure their safety. Only 1% of cases involved a female abuser. In general, the age of the abuser was older than previously reported with 18, 6% being under 20 years of age. The relationship between abused and abuser was similar to that described in the literature, as was the reaction of the family against the abuser. 27,4% were prosecuted and of those that appeared in court 7 4, 5% were convicted. Further comparison of the following sub-groups of abused children are presented: male and female, young and old, intrafamilial and extrafamilial abuse, a single episode of abuse and repeated abuse.